If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(3x + -1) = 4(3x + -1) Reorder the terms: 3(-1 + 3x) = 4(3x + -1) (-1 * 3 + 3x * 3) = 4(3x + -1) (-3 + 9x) = 4(3x + -1) Reorder the terms: -3 + 9x = 4(-1 + 3x) -3 + 9x = (-1 * 4 + 3x * 4) -3 + 9x = (-4 + 12x) Solving -3 + 9x = -4 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. -3 + 9x + -12x = -4 + 12x + -12x Combine like terms: 9x + -12x = -3x -3 + -3x = -4 + 12x + -12x Combine like terms: 12x + -12x = 0 -3 + -3x = -4 + 0 -3 + -3x = -4 Add '3' to each side of the equation. -3 + 3 + -3x = -4 + 3 Combine like terms: -3 + 3 = 0 0 + -3x = -4 + 3 -3x = -4 + 3 Combine like terms: -4 + 3 = -1 -3x = -1 Divide each side by '-3'. x = 0.3333333333 Simplifying x = 0.3333333333
| .10y-5=15 | | 10d+4+d=180 | | 45-3.5x=25 | | Y=4x-x-11 | | 16+.15x=.25x | | 14x-9=8+21x | | 13p-6=33 | | -9m-9=4 | | 30526-x=155528 | | 3(x+8)+14=2 | | 180=8x+120+7x | | 5b+15n=50 | | 6-.5x=10 | | -3y-9(3y-5)=-6+7(-7-y) | | 3x^2-13x-66=0 | | x+20+x-15+x-45=180 | | (0.6x^4)(0.2x^6)= | | 45+.25x=40+.30x | | 2(y-8)=6y-28 | | 40.25x=40+.30x | | .6x-6=7.2 | | 7u+4=3(u-4) | | 3(2x+4)=4+6x+12 | | -2(w+6)=-4w-16 | | Y-X=V | | 42=13+x+12 | | 17.50(x+400)=315 | | N-8n= | | 12+x+7=26 | | (6x+4)2=-16 | | 4.95+1.25n=10 | | Z-17=34 |